2019
DOI: 10.1038/s41598-019-55637-2
|View full text |Cite
|
Sign up to set email alerts
|

Highly flexible and stable resistive switching devices based on WS2 nanosheets:poly(methylmethacrylate) nanocomposites

Abstract: This paper reports data for the electrical characteristics and the operating mechanisms of flexible resistive switching devices based on WS2 nanosheets (NSs) dispersed in a poly(methyl methacrylate) (PMMA) layer. The ON/OFF ratio of the memristive device based on an Al/WS2 NSs:PMMA/indium tin oxides (ITO) structure was approximately 5.9 × 104. The memristive device based on the WS2 NSs also exhibited the bipolar switching characteristics with low power consumption and great performance in the bent state with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 36 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…Based on the above observations, a schematic of the physical charge transport mechanism through the energy band structures of Al/MoSe 2 @PMMA/ITO is proposed in Figure . Here, the PMMA layer has a wide band gap compared to MoSe 2 and acts as the charge-blocking material. , On the other hand, the MoSe 2 NFs work as charge-trapping sites, where the injected electrons are trapped, as shown in Figure b. Beyond the SET voltage, the concentration of electrons increases significantly to fill all of the trap sites, which allows for a continuous flow of charge carriers between the electrodes leading to Ohmic conduction and switching to LRS .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above observations, a schematic of the physical charge transport mechanism through the energy band structures of Al/MoSe 2 @PMMA/ITO is proposed in Figure . Here, the PMMA layer has a wide band gap compared to MoSe 2 and acts as the charge-blocking material. , On the other hand, the MoSe 2 NFs work as charge-trapping sites, where the injected electrons are trapped, as shown in Figure b. Beyond the SET voltage, the concentration of electrons increases significantly to fill all of the trap sites, which allows for a continuous flow of charge carriers between the electrodes leading to Ohmic conduction and switching to LRS .…”
Section: Resultsmentioning
confidence: 99%
“…WS 2 is one of the candidates for memristors due to its advantages, such as its layered structure, simple composition, easy manufacturing, and high compatibility with CMOS technology [70]. Lee et al [71], based on the WS 2 , designed an Al/WS 2 NSs:PMMA/indium tin oxides (ITO) structure device with a radius of curvature of 10 mm, which has an on/off ratio up to 10 3 at 0.5 V. The memristive device also exhibits low power consumption and high-performance bipolar switching characteristics at the bending state with a radius of curvature of 10 and 20 mm. He et al [72] prepared graphene//WSe 2-x O y /graphene flexible full two-dimensional memristors.…”
Section: Two-dimensional Materials: Flexible Memristormentioning
confidence: 99%
“…Hence, it can be considered that there is a formation of a conductive filament during the electroforming process. 7,46 At first, when the negative voltage is applied from 0 to −1 V at the FTO/TiO 2 interface, the O 2− ion starts migrating from the bottom FTO region resulting in the formation of a conductive filament. This filament is responsible for switching the device from HRS to LRS through migration of oxygen ions.…”
Section: Mechanism For Resistive Switchingmentioning
confidence: 99%
“…Moreover, the TiO 2 nanosheet-based materials have shown impressive results in lithium-ion batteries, enhancing solar cell performance, photocatalytic activity, etc. The 2D TiO 2 nanosheets when combined with organic/inorganic materials at both molecular and nanoscale level can bring out desirable tailor-made properties for a wide range of applications. For example, it has been shown that the diffusion of lithium ions was significantly enhanced due to the TiO 2 nanosheets, which in turn increased the lithium-ion storage properties in SnO 2 mesophere-TiO 2 nanosheet composites . PbS quantum dots and TiO 2 nanosheet heterojunction showed the increased power conversion efficiency of solar cells by 4.73 %, due to high surface area and high reactivity facets of the 2D TiO 2 nanosheets .…”
Section: Introductionmentioning
confidence: 99%